Thermochemical liquefaction of wood and coconut shell sawdust - Villena, Cesar C. (Animo Repository, 1998)
Thermochemical liquefaction experiments are done on wood and coconut shell sawdust using a high temperature, high pressure reactor. Three 25-gram samples consisting of wood, coconut shell, 1:1 combination of both were processed at 250 degrees Centigrade and 300 degrees Centigrade for one hour using 1 percent catalyst at 450 psig. initial pressure.The results show that coconut shell sawdust run at 250 degrees Centigrade have the most yield measured at 49.2 percent with a conversion of 86.4 percent. This, however, decreased significantly as the temperature was raised to 300 degrees Centigrade where the yield dropped to 25.6 percent and the conversion at 59.2 percent. Wood sawdust, on the other hand was relatively affected by the different reaction temperatures as its yield only dropped from 40 percent to 38.4 percent. The wood-coconut shell combination showed the least prospective of the samples studied.